ANALISIS DAMPAK PEMBANGUNAN PLBN SKOUW TERHADAP JUMLAH KUNJUNGAN WISATA, PENDAPATAN PEDAGANG DAN TATA KELOLA PASAR - Pondayar, Editha Magreth; Widanta, A.A Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Indonesia country has territorial borders with various countries. The land border directly adjacent of Malaysia, Papua New Guinea and Timor Leste. These boundaries spread across the islands of Kalimantan, Papua and East Nusa Tenggara. The RI-PNG Border Area in Skouw Jayapura Papua only area within the administrative area of ??the provincial capital in Indonesia so very strategic to be developed as trade area. This supported by traditional skouw market which is the center of cross-border trade for goods and services between RI-PNG. The purpose of this study was to analyze: 1) The number of tourist visits after the construction of the Skouw state border crossings. 2) Merchants' income in the Skouw market after the construction of the Skouw cross border posts. 3) Market governance after the construction of Skouw cross border posts. The samples taken was 74 traders with non probability sampling techniques. The analysis technique used non-parametric statistical test and the Mc Nemar test. Based on the results of the analysis that has been carried out, it is concluded that the number of tourist visits, merchant income and market management has increased after the construction of the Skouw cross-border post. Keywords: Land Border, Cross Border Post, Cross Border Trade.